Intraspecific competition counters the effects of elevated and optimal temperatures on phloem-feeding insects in tropical and temperate rice - Horgan, Finbarr G.; Arida, Arriza; Ardestani, Goli; Almazan, Maria Liberty P. (Public Library of Science, 2020)
The direct effects of rising global temperatures on insect herbivores could increase damage to cereal crops. However, the indirect effects of interactions between herbivores and their biotic environment at the same temperatures will potentially counter such direct effects. This study examines the potential for intraspecific competition to dampen the effects of optimal temperatures on fitness (survival × reproduction) of the brown planthopper, Nilaparvata lugens [BPH] and whitebacked planthopper, Sogatella furcifera [WBPH], two phloem-feeders that attack rice in Asia. We conducted a series of experiments with increasing densities of ovipositing females and developing nymphs on tropical and temperate rice varieties at 25, 30 and 35°C. Damage from planthoppers to the tropical variety was greater at 30°C compared to 25°C, despite faster plant growth rates at 30°C. Damage to the temperate variety from WBPH nymphs was greatest at 25°C. BPH nymphs gained greater biomass at 25°C than at 30°C despite faster development at the higher temperature (temperature-size rule); however, the effect was apparent only at high nymph densities. WBPH survival, development rates and nymph weights all declined at ≥ 30°C. At about the optimal temperature for WBPH (25°C), intraspecific crowding reduced nymph weights. Temperature has little effect on oviposition responses to density, and intraspecific competition between females only weakly counters the effects of optimal temperatures on oviposition in both BPH and WBPH. Meanwhile, the deleterious effects of nymph crowding will counter the direct effects of optimal temperatures on voltinism in BPH and on body size in both BPH and WBPH. The negative effects of crowding on BPH nymphs may be decoupled from resource use at higher temperatures.